CORNELIUS BERTRAM AND CARLO SIGONIO: CHRISTIAN HEBRAISM'S FIRST POLITICAL SCIENTISTS. - Ziskind, Jonathan R. (Journal of Ecumenical Studies)
Focuses on the creation of religious books by several political scientists on an analysis of the ancient Hebrew polity in Europe. Similarity of the methodologies used by the political scientists; Explanation on the concept of antiquity; Characterization of humanism.